2016
DOI: 10.1525/jsah.2016.75.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Skin, Clothing, and Dwelling

Abstract: Gottfried Semper is often credited with originating the concept of the building as skin in architectural theory, but an alternative trajectory of this idea can be found in the mid-nineteenth-century science of hygiene. In Skin, Clothing, and Dwelling: Max von Pettenkofer, the Science of Hygiene, and Breathing Walls, Didem Ekici explores the affinity of skin, clothing, and dwelling in nineteenth-century German thinking, focusing on a marginal figure in architectural history, physician Max von Pettenkofer (1818–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Indoor air hygiene efforts in Western countries in the 19th century also coincided with the need for improved sanitation in urban areas and for reducing the incidence of disease as urban populations grew. According to Ekici,5 Specifically, he showed that microscopic life could only originate from other life and could not be generated from inorganic substances or non-living organic debris. This discovery was a major scientific milestone.…”
Section: Indoor Air: a Short History Of Holistic And Reductionistic Amentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor air hygiene efforts in Western countries in the 19th century also coincided with the need for improved sanitation in urban areas and for reducing the incidence of disease as urban populations grew. According to Ekici,5 Specifically, he showed that microscopic life could only originate from other life and could not be generated from inorganic substances or non-living organic debris. This discovery was a major scientific milestone.…”
Section: Indoor Air: a Short History Of Holistic And Reductionistic Amentioning
confidence: 99%
“…Indoor air hygiene efforts in Western countries in the 19th century also coincided with the need for improved sanitation in urban areas and for reducing the incidence of disease as urban populations grew. According to Ekici, “ Starting in the 1830s and 1840s, a growing number of middle‐class reformers in Germany, Britain, France, and the United States raised public awareness of health issues. Their agenda included all aspects of urban design, from sewers and water supplies to street layouts and the construction of healthy buildings … When hygiene first emerged as a new science, it was closely associated with physiology.…”
mentioning
confidence: 99%